Teaching mathematics in ‘different tongues’: An analysis of mathematics anxiety and proficiency among elementary-grade learners - Bacolod-Iglesia, Aina Bael; Dundain, Hangeline Habibulla; Vegare-Miñoza, Manilyn; Casimiro, Arvin Barretto (Linguistics and Culture Review, 2021)
Language choice in teaching mathematics is a legitimate area of concern. It is noted that tension exists in classrooms where mathematics is taught in a language different from the first language spoken by the learners (Martínez & Dominguez, 2018). It is then a logical supposition to make that if students in mathematics classes are taught and tested in a language that is not their native their scores and proficiency levels may not be a true measure of their abilities, but a reflection of their mastery of the language used as medium of instruction (Haag, Heppt, Stanat, Kuhl & Pant, 2013). Against this contention, this study is conducted to determine the mathematics proficiency and anxiety of students learning mathematics across different local languages. In addition, the study analyzed whether significant differences exist in the investigated variables across gender. The study disclosed interesting results which were discussed herein.